Clinical Features of Pandrug-Resistant Acinetobacter Baumannii Bacteremia at a University Hospital in Taiwan - 郭律成(Lu-Cheng Kuo); 余忠仁(Chong-Jen Yu); 李麗娜(Li-Na Lee); 王竣令(Jiun-Ling Wang); 王鶴健(Hao-Chien Wang); 薛博仁(Po-Ren Hsueh); 楊泮池(Pan-Chyr Yang) (Journal of the Formosan Medical Association, 2003)
The number of infections caused by Acinetobacter baumannii has increased in recent years and the emergence of pandrug-resistant A. baumannii (PDRAB) has been observed in Taiwan. The aim of this study was to evaluate the clinical features and outcomes of patients with bacteremia due to PDRAB. From January 1999 to April 2002, 30 patients with PDRAB bacteremia were treated. We analyzed the clinical characteristics of these patients, including gender, underlying diseases, clinical manifestations, antibiotic treatment, and outcome. Bacteremia developed an average of 33 days after hospitalization and was hospital acquired in all cases. The source of bacteremia was identified in 19 patients (63.3%) and was most commonly from the respiratory tract. The overall mortality was 60% (18 patients). Among these, the cause of death was directly related to PDRAB bacteremia in 12. Underlying heart disease, shock, resuscitation, acute respiratory distress syndrome, mechanical ventilation, and multiple organ dysfunction score (MODS) were significant predictors of mortality after the development of PDRAB bacteremia. No specific antimicrobial therapy appeared to be effective. Clinical outcomes of patients with PDRAB bacteremia were related to the medical conditions of the patients at the time of development of bacteremia and could be predicted by the MODS. The only way to limit the spread is through strict preventive measures for nosocomial infection and antibiotic control.